The Influence of Using UKM Digital Payment Systems on the Purchase Interest of 2022 Economic Education Study Program Students, Medan State University - Rinaldi, Muammar; Sinaga, Anisa Fitria; Lubis, Atika Atayarisah; Amelia, Regita; Saputra, Firman; Manurung, Eka Valentina (Outline Publisher, 2025)
Technological advances in the field of payment systems have also changed the function of cash from the main means of payment to a non-cash payment method that is more efficient, practical and economical. This research aims to analyze the influence of the use of digital payment systems in UKM on the buying interest of Economic Education Study Program students class of 2022. This research uses a quantitative research design, which uses numerical data to assess conclusions. The population of this research are students of the 2022 Stambuk Economic Education study program, Medan State University who are interested in using a digital payment system.. The research used 30 samples. Based on the research results, it shows that the use of digital SME payment systems affects students' buying interest, where the results of the partial regression test (T test) are at a significant level of 0.05 with a T value of 8.461 with a significance of 0.000 < 0.05. Meanwhile, the Ttable value is 2.034. Therefore, Ha is accepted because the tcount value is 8.461 > table 2.034 so it can be concluded that there is a significant influence between the use of digital SME payment systems on the student purchasing interest variable. The correlation coefficient value of 0.827 indicates that the two variables have a close relationship, where an increase in the use of digital payment systems will be followed by an increase in students' buying interest.